2008
DOI: 10.1538/expanim.57.101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathological Evaluation of MDP/Collagen Induced Arthritis Rat Model (MCIA) after Treatment with Urtica Dioica, Plantago Major and Hypericum Perforatum L Herbal Mixture

Abstract: This study was done to assess the effects of Urtica dioica, Plantago major and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The induction of RA was evaluated clinically by the observation of edema and erythema in the tibia-fibula (knee) and talocrural (ankle) joints 8,9,10. The measurement of edema in the tibia-fibula joint in the flexed position and in the talocrural joint in the neutral position was performed using a digital caliper ( Vonder ) one week after injection of the solution and on the day the animals were euthanized 7,11.…”
Section: Methodsmentioning
confidence: 99%
“…The induction of RA was evaluated clinically by the observation of edema and erythema in the tibia-fibula (knee) and talocrural (ankle) joints 8,9,10. The measurement of edema in the tibia-fibula joint in the flexed position and in the talocrural joint in the neutral position was performed using a digital caliper ( Vonder ) one week after injection of the solution and on the day the animals were euthanized 7,11.…”
Section: Methodsmentioning
confidence: 99%
“…The Phytochemical analysis of U.dioica showed it contain (alkaloid, flavonoid, terpenoid, tannin, phenolic and several of minerals elements) which has hepatoprotective activity through its free radical scavenger. 14,43,44 The previous study has suggested that regucalcin can directly bind and stimulate Ca +2 pump activity. 45,46 Therefore, the phenolic compound of U.dioica may play an important role in decreasing Ca +2 pumping activity and maintain both cell homoeostasis and function that led to decrease regucalcin level [47][48][49] .…”
Section: Study Of the Effect Of Udioica On Regucalcin Levelmentioning
confidence: 99%
“…Each rat was immunized with 0.1 ml of the cold emulsion (0.1 mg CII) using a Hamilton glass syringe by subcutaneous injection into the base of the tail, 2-3 cm from the body on day 0. Rats were boosted subcutaneously by a second injection of 0.1 ml (0.1 mg CII) of the collagen emulsion also into the base of the tail 7 days after the first immunization [18,19].…”
Section: Induction Of Type II Collagen-induced Arthritismentioning
confidence: 99%
“…The arthritis score for each mouse was the sum of all paw scores where the highest score per mouse would be 16 [19].…”
Section: Clinical Assessment Of Arthritismentioning
confidence: 99%
See 1 more Smart Citation